2022
DOI: 10.3389/fpsyg.2022.900830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agile Learning on Innovative Behavior: A Moderated Mediation Model of Employee Engagement and Perceived Organizational Support

Abstract: This study analyzed learning agility, employee engagement, perceived organizational support (POS), and innovative behavior related to the development of innovative environment and the mental and psychological health of employees. A substantial body of research has examined the antecedents of innovative behavior of employees in their work environment, but our current understanding of how learning and motivational aspects of employees synthetically influence the innovative behavior remains incomplete. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 111 publications
0
5
0
1
Order By: Relevance
“…individu yang memiliki keterampilan rendah atau pekerjaan manual rentan digantikan oleh teknologi (Dahlin, 2019). Sebagai pekerja di organisasi pada akhirnya melakukan inovasi, perilaku inovasi individu merupakan prasyarat untuk inovasi organisasi yang sukses (Jo & Hong, 2022). Perilaku kerja inovasi ini sering disebut sebagai innovative behavior.…”
Section: Pendahuluanunclassified
“…individu yang memiliki keterampilan rendah atau pekerjaan manual rentan digantikan oleh teknologi (Dahlin, 2019). Sebagai pekerja di organisasi pada akhirnya melakukan inovasi, perilaku inovasi individu merupakan prasyarat untuk inovasi organisasi yang sukses (Jo & Hong, 2022). Perilaku kerja inovasi ini sering disebut sebagai innovative behavior.…”
Section: Pendahuluanunclassified
“…The four dimensions of LA are directly related to innovative behavior. In particular, mental agility, which is characterized by curiosity and comfort with ambiguity and complexity; people agility, which is related to open-mindedness, flexibility, and communication skills; change agility, which includes experimenting, trying new things, and easily accepting challenges; and result agility, which is related to creating results, can serve as a key resource for innovative behavior (Jo & Hong, 2022). Several empirical studies have shown that LA can increase IWB (Jo & Hong, 2022;Putri & Suharti, 2021;Riswan et al, 2021).…”
Section: Learning Agility and Innovative Work Behaviormentioning
confidence: 99%
“…According to Li et al (2019) IWB contributes to increasing worker innovation and creativity. IWB can be grown by several factors such as learning agility (Jo & Hong, 2022;Putri & Suharti, 2021); employee engagement (Contreras et al, 2022;Ali et al, 2022;Sari et al, 2021;Ranihusna et al, 2021); leader member-exchange and job involvement (Sahaming et al, 2022). Every employee's innovative actions at work can lead to the discovery and introduction of new ideas that are profitable for the organization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations